Keller-Box Study on Casson Nano Fluid Flow Over a Slanted Permeable Surface with Chemical 4 Reaction - Rafique, Khuram; Anwar, Muhammad Imran; Misiran, Masnita (Asia Pacific Publisher, 2019)
In this problem, examination of Casson Nanofluid boundary layer stream over linear slanted 13 extending sheet by fusing the chemical reaction and heat generation impacts are under thought. 14 Nanofluid demonstrate in this examination is developed on Buongiorno model for the warm 15 efficiencies of the liquid streams in the presence of Brownian movements and thermophoresis 16 impacts. The nonlinear issue for Casson Nanofluid stream over slanted channel is displayed to 17 ponder the heat and mass exchange wonder by considering portant stream parameters to 18 strengthened boundary layers. The governing nonlinear partial differential equations are 19 decreased to nonlinear normal differential equations and afterward illustrated numerically by 20 methods for the Keller-Box plot. An examination of the set up results in the absence of the joined 21 impacts is performed with the accessible outcomes of Khan and Pop [1] and set up in a decent 22 contract. Numerical and graphical outcomes are additionally exhibited in tables and graphs